Тритикале як сировина для виробництва цільнозернових продуктів: перспективи і виклики - Желєзна, Валерія Валеріївна; Zheliezna, Valeriia; Нос, О. М.; Nos, O. (Запоріжжя: ТДАТУ, 2025)
UA: Тритикале – міжродовий гібрид пшениці та жита, що був створений як перспективна зерно-ва культура для поєднання високих хлібопекарських якостей пшениці та стійкості жита до несприятливих умов вирощування. У сучасному агропромисловому комплексі тритикале займає особливе місце серед зер-нових культур, оскільки характеризується підвищеною адаптивністю до різних кліматичних зон, високою врожайністю, стійкістю до шкідників і хвороб, а також збалансованим біохімічним складом зерна. У зв’язку з глобальними тенденціями до переходу на здорове харчування, зростанням попиту на продукти з високим умістом харчових волокон та біологічно активних речовин тритикале розглядається як перспективна сирови-на для виробництва цільнозернових продуктів.У статті проведено комплексний аналіз харчового потенціалу тритикале, особливостей його обробки та перспектив технологічного впровадження. Окрему увагу приділено досвіду вітчизняних і зарубіжних науков-ців, які зробили внесок у вивчення складу, властивостей та методів переробки цієї культури. Запропоновано шляхи вирішення наявних проблем і сформовано науково обґрунтовану стратегію розроблення технологій виробництва цільнозернових продуктів із зерна тритикале. /// EN: Triticale is an intergeneric hybrid of wheat and rye, developed to combine the high baking qualities of wheat with the increased resistance of rye to unfavorable growing conditions. In modern agro-industrial production, this crop occupies a special place among cereals due to its high ecological plasticity, resistance to diseases and pests, and ability to ensure stable yields in diverse climatic conditions. The biochemical composition of triticale grain is characterized by a balanced content of protein, dietary fiber, minerals, and vitamins, making it a valuable raw material for the food industry and a promising component in the diet of healthy nutrition.Considering the global trends toward an increased demand for foods with high nutritional and biological value, triticale is regarded as one of the most promising crops for the production of whole-grain bakery and dietary products. The use of the grain in its whole-grain form makes it possible to preserve its beneficial components to the maximum extent and to expand the range of functional food products.The article presents a comprehensive analysis of the nutritional potential of triticale, the peculiarities of its technological processing, and the possibilities of its industrial application. The scientific contributions of domestic and foreign researchers regarding the study of the grain composition, biological properties, and processing methods have been analyzed. The main challenges limiting the wide use of this crop in the food industry have been identified, including the imperfection of milling technologies and the need to adapt traditional recipes. Solutions to these issues are proposed, and the prospects for developing new technologies for the production of whole-grain products from triticale grain are substantiated, combining high nutritional value, good organoleptic properties, and compliance with modern requirements of rational nutrition.
Triticale as a raw material for whole grain products: prospects and challenges
Keywords: тритикале; пшениця; жито; технологічні властивості; хімічний склад; triticale; wheat; rye; technological properties; chemical composition